An Assessment of the Sustainability of Lignocellulosic Bioethanol Production from Wastes in Iceland - Sahar Safarian; Runar Unnthorsson (Energies, 2018)
This paper describes the development of a model to comprehensively assess the sustainability impacts of producing lignocellulosic bioethanol from various types of municipal organic wastes (MOWs) in Iceland: paper and paperboard, timber and wood and garden waste. The tool integrates significant economic, energy, environmental and technical aspects to analyse and rank twelve systems using the most common pretreatment technologies: dilute acid, dilute alkali, hot water and steam explosion. The results show that among the MOWs, paper and paperboard have higher positive rankings under most assessments. Steam explosion is also ranked at the top from the economic, energy and environmental perspectives, followed by the hot water method for paper and timber wastes. Finally, a potential evaluation of total wastes and bioethanol production in Iceland is carried out. The results show that the average production of lignocellulosic bioethanol in 2015 could be 12.5, 11 and 3 thousand tons from paper, timber and garden wastes, respectively, and that production could reach about 15.9, 13.7 and 3.7 thousand tons, respectively, by 2030.